The preoperative triglyceride-glucose index has a positive effect on predicting the risk of short-term restenosis after carotid artery stenting: a retrospective cohort study - Zhao, Shan-shan; Jiang, Zhen-zhen; Wei, Bo; Zhu, Jian-bo; Liu, Xia-tian (Frontiers in Neurology, 2023)
Background Increasing evidence suggests that insulin resistance is linked to cardiovascular disease and atherosclerosis. The triglyceride–glucose (TyG) index has proven to be a convincing marker to quantitatively evaluate insulin resistance. However, there is no relevant information about the relationship between the TyG index and restenosis after carotid artery stenting. Methods A total of 218 patients were enrolled. Carotid ultrasound and computed tomography angiography were used to evaluate in-stent restenosis. A Kaplan–Meier analysis and Cox regression method were performed to analyze the correlation between TyG index and restenosis. Schoenfeld residuals were used to determine the proportional-hazards assumption. A restricted cubic spline method was used to model and visualize the dose–response relationship between the TyG index and the risk of in-stent restenosis. Subgroup analysis was also performed. Results Thirty-one participants (14.2%) developed restenosis. The preoperative TyG index had a time-varying effect on restenosis. Within 29 months post-surgery, an increasing preoperative TyG index was linked to a significant increased risk of restenosis (hazard ratio: 4.347; 95% confidence interval 1.886–10.023). However, after 29 months, the effect was decreased, although not statistically significant. The subgroup analysis showed that the hazard ratios tended to be higher in the age ≤ 71 years subgroup (p < 0.001) and participants with hypertension (p < 0.001). Conclusion The preoperative TyG index was significantly associated with the risk of short-term restenosis after CAS within 29 months post-surgery. The TyG index may be employed to stratify patients based on their risk of restenosis after carotid artery stenting.